People - Marine Mammal Interactions - Mark P. Simmonds (Frontiers Research Topics, 2017)
Our relationships with marine mammals are complex. We have used them as resources, and in some places this remains the case; viewed them as competitors and culled them (again ongoing in some localities); been so captivated and intrigued by them that we have taken them into captivity for our entertainment; and developed a lucrative eco-tourism activity focused on them in many nations. When we first envisaged this special topic, we had two overarching aims: Firstly, we hoped to generate critical evaluation of some of our relationships with these animals. Secondly, we hoped to attract knowledgeable commentators and experts who might not traditionally publish in the peer-reviewed literature. We were also asking ourselves a question about what responsibility mankind might have to marine mammals, on our rapidly changing planet? The answer to the question; can, or should, humans have responsibility for the lives of marine mammals when they are affected by our activities? - is, in our opinion, 'yes' - and the logical progression from this question is to direct research and effort to understand and optimise the actions, reactions and responses that mankind may be able to take. We hope that the papers in this special issue bring some illumination to a small selection of topics under this much wider topic area, and prove to be informative and stimulating.